Fracisco Suárez and Human Rights - Ibáñez Ruiz del Portal, Eduardo (Pensamiento. Revista de Investigación e Información Filosófica, 2018)
Jesuit Francisco Suárez as eminent theologian, philosopher and jurist of his time plays an important role as a precedent in the construction of the categories of modern thought. One of these categories, not contemporary of Francisco Suárez, are human rights. Many authors anticipate some of its fundamental elements already in the thinking around the Law developed by Francisco Suárez in his main treatises on legal and political philosophy such as De Legibus and Defensio fidei. In this article we will try to connect the virtuality of the suarist approach in the field of human rights, exploring in his work these antecedents and the direction in which they are directed, as well as the possibilities of dialogue that opens around the construction of the conception of human rights in the current context.
Keywords: Francisco Suárez; human rights; modernity; ignatian matrix cultural